An Evaluation of Previously Undiagnosed Childhood Primary Headache Cases Through Their EEG and MR Findings - Selcan Öztürk; Erdal Komut (Journal of Pediatric Research, 2024)
Aim: Headaches are a major cause of presentations to pediatric neurology clinics, the majority being primary. Although diagnosis is mostly based on medical history and physical examination, imaging methods and electroencephalography (EEG) are used for differential diagnosis or identifying accompanying conditions. We evaluated cases of primary headache presenting to a newly established pediatric neurology clinic in July-December 2022 and compared their magnetic resonance imaging (MRI) and EEG findings. Materials and Methods: Individuals presenting with headaches were first classified as primary or secondary headaches, and patients with primary headaches were included as migraine or tension-type headaches (TTH). Two hundred four patients presented but only fifty migraines and 50 TTH patients, who had EEG and MRI, met the study criteria. Results: Greater photophobia, phonophobia, and family histories were present in the migraineurs, while attack frequencies were higher and durations shorter in the TTH group (p=0.025, p=0.001, respectively). Pain was generally throbbing in character in the migraine patients and compression in the TTH cases. No pathology was encountered in the MRIs of 90% of the migraine patients and 94% of the TTH group. While no pathology was detected at EEG in most cases, sharp spike-wave activity was determined in 10% of the migraine patients and in 2% of the TTH group. Conclusion: MRI and EEG are not generally required in the diagnosis of primary headaches once a detailed history and physical examination have been performed. While the majority of brain MRI requests are of no particular diagnostic value, unnecessarily requested EEGs can lead to misdiagnoses. It is crucially important to ensure that patients are closely monitored and that unnecessary requests are avoided.